Blended Learning Model in Improving 4C Abilities of Information System Students - Ratih Purwasih; Rahimullaily Rahimullaily; Ade Irma Suryani (Lembaga Penelitian dan Pengabdian kepada Masyarakat, 2021)
Blended learning in this study combined face-to-face online learning and independent learning such as interactive media and zoom meeting application. This study aims to obtain the comparison of implementation blended learning in improving 4C abilities (critical thinking, creative, communication, and collaboration) system information students in English debate activity before and after the treatment. Furthermore, preliminary data from the subjects of this study before blended learning treatment showed an average value of < 55, and this value was categorized as “less”. Therefore, this research is a type of quantitative research using pre-experimental research method. The data were calculated by using SPSS. Research results indicated an increase in the students’ 4C abilities after implementing the blended learning model. The average increase of creativity was 43.79%, with an estimated increase is 39.89%. Critical thinking was 45.08%, with an estimate of 47.78%. Collaboration had 38.26%, with an estimate of 43.03%. At the same time, communication reached 38.32% with an estimation of 43.40%. Based on these results, the highest 4C increase was in critical thinking abilities compared to other abilities.